Bingo project: climate change and the groundwater component of the water cycle - Novo, M. E. (2017)
Climate change is bound to impact the water cycle and water availability, compounding the sustainable management of its quantity and quality. Groundwater is bound to suffer the impacts of climate change, coupled with those of land use changes, population and its lifestyles evolution. Climate change studies normaly have a 50 to 100 years horizon, which is a challenge for decision makers, who usually rely on relatively short therm data and projections to implement their management policies. BINGO Project tries to address this gap, by providing information of climate change impacts, including those of extreme events, on the water cycle for the short-tomedium term. Climate change impacts on groundwater rely on mathematical modeling, using recharge projections obtained from the climate forecasts of the Regional Climate Models set up for Europe. Sea level change is also a component of this analysis and its ensuing impacts of saltwater intrusion on the coastal and estuarine areas of Aluviões do Tejo and Bacia do Tejo-Sado/Margem Esquerda aquifers.